Chewstick trauma-induced oral squamous cell carcinoma - Ashutosh Nirola; Ranchana Garg (Wolters Kluwer Medknow Publications, 2018)
Oral carcinoma is one of the most prevalent cancers and one of the 10th most common causes of death worldwide. Oral squamous cell carcinoma accounts for nearly 90% of all oral carcinomas. Squamous cell carcinoma is the malignant neoplasm of mucosal origin. The etiology of squamous cell carcinoma is multifactorial. The use of tobacco and betel quid, heavy alcohol drinking, intake of diet low in fresh fruits and vegetables, viruses, trauma, and genetics are considered as possible risk factors. Early diagnosis of oral squamous cell carcinoma plays an important role in improving prognosis and reducing morbidity and mortality associated with it. It can be managed by surgery, chemotherapy, radiotherapy, or combination of all these, but regardless of its treatment modality, the 5-year survival rate is poor at about 50%. This case report demonstrates a case of oral squamous cell carcinoma induced by Chewstick trauma with a history of no deleterious habits and is confirmed by clinical and histopathological examination.